(untitled) (European Bison Conservation Newsletter, 2009)
The success of European bison restitution in Poland is treated as the very good example of conservation project and gained experience is share all over the Europe. It does not mean that on the way there was no failures as well as mistakes in the process. One of examples is development and collapse of bison population in Forestry Brzegi Dolne in Bieszczady. The European bison herd created in 1978 after 20 year achieved the number of 32 individuals. During five years because of bovine tuberculosis the herd was completely eliminated and now there is no European bison in the region.